Analysis of isoaspartate in peptides by electrospray tandem mass spectrometry - Lehmann, Wolf-Dieter; Pipkorn, Rüdiger; Bossemeyer, Dirk; Kinzel, Volker (Protein science, 2008)
In view of the significance of Asn deamidation and Asp isomerization to isoAsp at certain sites for protein aging and turnover, it was desirable to challenge the extreme analytical power of electrospray tandem mass spectrometry (ESI‐MS/MS) for the possibility of a site‐specific detection of this posttranslational modification.
First published online: 31 December 2008
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 23.02.2021